Clima organizacional na Universidade Federal da Paraíba: a percepção dos servidores lotados no Departamento de Ciências Jurídicas - Silva, Emanuel Caetano da (2020)
The main objective of the research was to investigate the perception of the organizational climate of the technical administrative and immediate superior employees, with capacity in the Department of Legal Sciences of the Federal University of Paraíba. The perception aimed at three axes: Federal University of Paraíba, the Department of Legal Sciences and the sectors of activity. The theory for the construction of the theme was developed in concepts related to organization, organizational environment, organizational culture, organizational climate and its transversality (culture, perception and satisfaction), the study of this theme in Higher Education Institutions and the climate research tool. Gerson Rizzatti's model (1995) was the main basis for designing the research. This work is of a qualitative and quantitative, exploratory, documentary and bibliographic nature. Data were collected for analysis using an electronic form. The sample had 20 servers in which it represented 91% of the research universe. The employees had the opportunity to demonstrate perceptions by categories of analysis concerning their organizational environment. On the other hand, it can be verified that at the Federal University of Paraíba this type of research is not usual, however, throughout the study it was found the importance of knowing about the organizational climate, as it became evident that institutions also need learn from your internal employees in order to understand their real needs. Finally, it was considered that in the three axes of investigation, the climate situation is favorable for the harmonic work environment, with a predominance of a positive climate.